2016
DOI: 10.1002/jez.2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Natural and Anthropogenic Sodium Channel Blockers Tetrodotoxin and Indoxacarb in Garter Snakes

Abstract: Synthetic chemicals, such as pesticides, are used in a variety of ways in the agricultural industry. Anthropogenic chemicals pose a unique challenge to organisms because of the lack of evolutionary history between the chemical and the organism. However, research has shown that some organisms have a resistance to these synthetic chemicals due to their evolved resistance to a natural compound with a similar structure or mode of action. Indoxacarb (INDOX) is a relatively new pesticide with a similar mode of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Differences in these responses may reflect species-specific physiological adaptations (Hopkins et al, 2016;Neuman-Lee et al, 2016a). We have shown that exposure to low concentrations of gamabufotalin elicits an increase in corticosterone in all three species groups.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Differences in these responses may reflect species-specific physiological adaptations (Hopkins et al, 2016;Neuman-Lee et al, 2016a). We have shown that exposure to low concentrations of gamabufotalin elicits an increase in corticosterone in all three species groups.…”
Section: Discussionmentioning
confidence: 81%
“…Vertebrates possess a suite of physiological responses to external challenges (Neuman-Lee et al, 2016a;Love and Williams, 2008;McEwen, 2007;Råberg et al, 1998), and the hypothalamic-pituitary-adrenal (HPA) axis constitutes one of the most conserved mechanisms underlying these responses (Wingfield, 2005;Wingfield and Romero, 2001). The HPA axis interacts with other physiological systems by activating and/or suppressing a physiological cascade that stimulates hormonal secretion from the adrenal glands (Dhabhar, 2009;Norris, 2006;Sapolsky et al, 2000).…”
mentioning
confidence: 99%